The Motifs of the Moon and Night in Contemporary Kazakh Youth Prose (Eurasian Journal of Philology Science and Education, 2025)
This study explores the artistic and semantic roles of the moon and night motifs in contemporary Kazakh youth prose. The relevance of the topic lies in the revival of mythological and mystical consciousness in literature, reflecting the spiritual quests of the modern individual. The motifs of the moon and night are not merely natural phenomena but serve as archetypal symbols that reveal characters’ inner turmoil, existential struggles, and spiritual transformation. The aim of the research is to provide a comprehensive analysis of the symbolic and semiotic functions of these motifs, their mythopoetic meanings, and their roles in plot development and character psychology. The study focuses on the works of Lyra Konys and Madina Omarova. The methodology includes mythopoetic, hermeneutic, comparative, and narratological analysis, incorporating the concepts of archetype and chronotope. The findings demonstrate that moon and night motifs construct a rich poetic and symbolic space, bridging national mythological memory with contemporary consciousness. This research systematizes mystical-symbolic elements in Kazakh prose and proposes a new theoretical approach to their literary analysis. Practically, the study serves as a valuable methodological resource for literary studies, cultural analysis, semiotics, and archetypal psychology.Key words: mysticism, motif, totem, symbol, myth.